2020
DOI: 10.1001/jamacardio.2019.4428
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pulmonary Hypertension With Clinical Outcomes of Transcatheter Mitral Valve Repair

Abstract: pHTN) is associated with increased risk of mortality after mitral valve surgery for mitral regurgitation. However, its association with clinical outcomes in patients undergoing transcatheter mitral valve repair (TMVr) with a commercially available system (MitraClip) is unknown.OBJECTIVE To assess the association of pHTN with readmissions for heart failure and 1-year all-cause mortality after TMVr. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study analyzed 4071 patients who underwent TMVr with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 21 publications
2
38
0
Order By: Relevance
“…While other studies have shown lower survival in patients with pre‐procedural severe PHT, 8,19 their survival was similar in our study. To further evaluate this issue, we performed a log‐rank analysis for patients who had improved their pulmonary pressure compared with patients whose sPAP had worsened or remained unchanged and showed that survival was similar.…”
Section: Discussionsupporting
confidence: 81%
“…While other studies have shown lower survival in patients with pre‐procedural severe PHT, 8,19 their survival was similar in our study. To further evaluate this issue, we performed a log‐rank analysis for patients who had improved their pulmonary pressure compared with patients whose sPAP had worsened or remained unchanged and showed that survival was similar.…”
Section: Discussionsupporting
confidence: 81%
“…8) For example, the absence of pulmonary hypertension is associated with better clinical outcomes following the MitraClip procedure. 12) Further investigations of key parameters to optimize patient selection for the MitraClip therapy are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…While EROA and RVol are the gold standards in MR severity assessment, the hemodynamic load (supported by RF assessment) and the extent and presence of advanced LV disease have recently been emphasized in recent randomized trials as key factors in determining the benefits of targeting the LV alone (OMT + CRT) or additionally the mitral valve (PMVR). However, clinical experience and published data also highlight the need to consider several additional factors, including the presence of severe RV dysfunction, advanced LV impairment (typically associated with very high BNP values), and an irreversible precapillary component of pulmonary hypertension ( 92 ), that can attenuate the benefit of PMVR and predict potential futility. Where doubt remains, functional testing to assess ventricular reserve ( 75 , 83 ) and dynamic RV-to-pulmonary circulation uncoupling ( 82 , 93 ) can be useful for further risk stratification.…”
Section: The Selection Of the Optimal Candidatementioning
confidence: 99%